Effect of transcranial direct current stimulation on puzzle-solving ability in stroke patients with cognitive dysfunction: A pilot study - Sanjiv Kumar; Saniya Sumant (Wolters Kluwer Medknow Publications, 2023)
PURPOSE: Stroke lies among the most disabling diseases and is world-wide a leading cause of death. Most of the stroke patients experience cognitive deficits associated with executive dysfunction (decision making, problem solving, working memory, and cognitive flexibility). Executive dysfunction in stroke makes the patients vulnerable to depression, anxiety as their daily activities like personal, social, cultural and occupational are severely affected. Thus, the dependency increases and their quality of life decreases. Problem solving is one such important executive function required in day-to-day life. Puzzle solving reflects onto ones problem-solving ability that requires understanding, conceptual knowledge recruitment, novel and insightful thinking, and processing a solution. The purpose of this study was to determine if noninvasive brain stimulation has any effect on puzzle-solving ability of stroke patients and to assess their performance on the same. METHOD: A 3-week interventional study on 11 stroke participants was done. The samples were assessed at baseline for cognitive impairment using Montreal Cognitive Assessment Scale. Participants with scores <26 were given a 30-piece Jigsaw Puzzle to solve and Wisconsin Card Sorting Test (WCST) was done, both at baseline and after 3 weeks. RESULTS: This study confirmed that there was improvement in the performance of solving the Jigsaw Puzzle after application of transcranial direct current stimulation (TDCS) (P = 0.005), but the scores on WCST showed no significant reliable change (P = 0.192). CONCLUSION: This study concluded that TDCS is effective in improving puzzle-solving ability in stroke patients.